2018
DOI: 10.1177/2058738418818630
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Panax notoginseng saponins in a rat model of severe acute pancreatitis occur through regulation of inflammatory pathway signaling by upregulation of miR-181b

Abstract: Panax notoginseng saponins are extracted from Chinese ginseng— Panax notoginseng Ledeb —and are known to have therapeutic anti-inflammatory effects. However, the precise mechanism behind their anti-inflammatory effects remains relatively unknown. To better understand how Panax notoginseng saponins exert their therapeutic benefit, we tested them in a rat model of severe acute pancreatitis (SAP). Rats received a tail vein injection of Panax not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(83 reference statements)
1
2
0
Order By: Relevance
“…Moreover, anti-inflammatory effects of genistein have also been proposed in lipopolysaccharide-induced inflammation in human endometrial cells (45). Recently, Liu et al have reported that Panax notoginseng saponins, extracted from Chinese ginseng, could reduce pancreatic inflammation by increasing miR-181b signaling (43). In our study, genistein treatment partially decreased miR-155 and increased miR-181b expression levels in the OVX.G group compared to OVX.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Moreover, anti-inflammatory effects of genistein have also been proposed in lipopolysaccharide-induced inflammation in human endometrial cells (45). Recently, Liu et al have reported that Panax notoginseng saponins, extracted from Chinese ginseng, could reduce pancreatic inflammation by increasing miR-181b signaling (43). In our study, genistein treatment partially decreased miR-155 and increased miR-181b expression levels in the OVX.G group compared to OVX.…”
Section: Discussionsupporting
confidence: 59%
“…More pertinently, genistein was found to have anticancer effects during the downregulation of miR-155 (22). Upregulation of miR-181b was associated with reduced edema and inflammatory cell infiltration during pancreatitis (43). It has been suggested that treatment with phytoestrogens could significantly decrease inflammatory biomarkers in estrogen-deficient rats (21).…”
Section: Discussionmentioning
confidence: 99%
“…The effective activities of saponins result from the hydrolytic aglycone and secondary aglycone [ 3 ]. Studies have found that PNS have beneficial effects on curing cardiovascular diseases [ 4 ] and show anti-osteoporosis [ 5 ], anti-cancer [ 6 ], anti-inflammatory [ 7 ] activities as well as protecting action with regard to liver and kidney [ 8 ]. However, PNS are unacceptable to consumers due to the bitter taste, are unstable in the stomach, and present low oral bioavailability [ 9 , 10 ], which limits their applications in the food industry.…”
Section: Introductionmentioning
confidence: 99%